Análise dos serviços terceirizados da engenharia Clínica - LOBATO, Rafael de Oliveira (2025)
With technological advancements in the healthcare sector, there is an increase in the complexity of maintaining new equipment. Thus, it increases the difficulty in managing medical equipment due to the need for increasingly skilled professionals to effectively carry out maintenance services. This difficulty is felt by professionals in Clinical Engineering (CE) who are responsible for the management and technical interventions: Preventive, Calibration, Electrical Safety Testing, and Corrective measures of medical-hospital equipment. (EMHs). The hospital institution must have financial sustainability for the operation of the business, and one way to contribute to this financial planning is related to the clinical engineering department, where the institution should consider the possibility of outsourcing its staff. This decision should be based on some points related to the EC sector, such as the specialization of maintenance for certain equipment, fluctuations in services, business expansion, and an increase in maintenance demands. Furthermore, with the outsourcing relationship, there arises the need to formulate a contract that addresses the actual needs of the institution regarding the management of the EMHs. This outsourcing of EC services must be monitored, and there should be performance indicators for that purpose. In light of the need to oversee these services, the role of the contract inspector emerges. In the current reality of outsourcing relationships between clinical engineering (CE) and healthcare establishments, the ideas previously presented are not always known or put into practice. Thus, this work aims to describe the contracting and monitoring of outsourced clinical engineering services in relation to the hospital institution.